SPECIFICITY OF OPERATION OF GENERAL INTEREST IN THE SERBIAWITH SPECIAL VIEW ON WATER MANAGEMENT - Rajnović, Ljiljana Dušan (Economics of Agriculture, 2020)
In this paper, the author presents the specificities of economic entities performing activities of general interest. In the Republic of Serbia, the state is responsible for the regulating of organized and permanent performance and the development of activities of general interest. In Serbia, the state ensures performing this activity through public companies or capital companies of which it is the sole founder, but it is possible to allow performing the aforementioned activities by entrusting them to a third party. The author conducted a survey related to the necessary conditions for performing activities of general interest by entrusting to a third party a few dozen of economic entities in Serbia. The author considers that, with fulfillment of prescribed conditions, the successful performing activities of general interest can be carried out by privately owned economic entities, since state-owned enterprises have proved to be insufficiently efficient and economical in practice.